2022
DOI: 10.30541/v42i4iipp.513-536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Privatisation on Employment and Output in Pakistan

Abstract: The paper aims to assess the impact of privatisation on employment and output in Pakistan. It uses edible oil and cement sectors as a case study in a pre- and post-privatisation comparative framework. Assessing the impact of privatisation in Pakistan is important at this juncture for two reasons. Firstly, the country is facing a severe economic crisis and privatisation forms an integral part of an array of reform measures recommended by multi-lateral donors as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hemming and Mansoor (1987) and Mansoor (1988bMansoor ( , 1988a also argue that ideally, the change of ownership should have no effect on fiscal deficit due to the fair market price of SOEs. Khan (2003) has also concluded that managers had incentives for upwards earnings management to increase the probability of privatisation. This is because after the initial shock of privatisation was over, they benefitted both in terms of better wages and increased employment opportunities.…”
Section: Incentives For Upward Earnings Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemming and Mansoor (1987) and Mansoor (1988bMansoor ( , 1988a also argue that ideally, the change of ownership should have no effect on fiscal deficit due to the fair market price of SOEs. Khan (2003) has also concluded that managers had incentives for upwards earnings management to increase the probability of privatisation. This is because after the initial shock of privatisation was over, they benefitted both in terms of better wages and increased employment opportunities.…”
Section: Incentives For Upward Earnings Managementmentioning
confidence: 99%
“…The fact is that in Pakistan, international financial aid was conditioned on the privatisation and restructuring of SOEs. Mirza (1995) gives a number of examples that highlight the role of international donors in privatisation in Pakistan. According to Khan (2003), since privatisation was an imported phenomenon in Pakistan, it had no clearly spelled out objectives initially. The government reports on privatisation do not list even a single objective until 1992 [Qureshi (1992)].…”
mentioning
confidence: 99%
“…Authors examined the incidence of earnings management around the time of the privatisation. Khan (2003) and Martin and Parker (1997) demonstrated that managers can benefit in the period of post privatisation period. It is because, the initial shock of privatisation is over, and they can benefit in terms of better wages or of the increase employment opportunities.…”
Section: Effect Of Privatizationmentioning
confidence: 99%
“…The immediate impact of privatisation and the consequences of private sector unemployment due to downsizing are unavoidable. This is responsible for increasing fears of job loss, particularly in the private sector (see Khan [2003] for a more detailed discussion on the impact of privatisation on employment). There is a modest amount of literature available supporting the statement that in the short run, privatisation grounds unemployment and fall in wages (Gupta et al 1999).…”
Section: Job Preference Equations: Probit Estimatesmentioning
confidence: 99%